The isokinetic strength profile of quadriceps and hamstrings in elite volleyball players - Hadzic, V.; Sattler, T.; Markovic, G.; Veselko, M.; Dervisevic, E. (Isokinetics and Exercise Science, 2010)
Knowledge of lower-extremity strength can be used in injury prevention, conditioning and rehabilitation of volleyball players. The goals were: (1) to describe the bilateral concentric and eccentric quadriceps (Q) and hamstrings (H) muscle function in volleyball players, (2) to evaluate the differences in Q and H strength, strength ratios and bilateral strength asymmetry among age groups, playing positions and playing levels, (3) to compare bilateral strength asymmetry in Q and H muscles in two different contraction modes. Ninety five professional male volleyball players were tested on an isokinetic machine at 60°/s to assess concentric and eccentric Q and H strength. We also calculated strength ratios and bilateral strength asymmetries. MANOVAs indicated significant main effect of playing level on relative PT (p = 0.001) and strength ratios (p < 0.05). International-level players had significantly (p < 0.05) higher H strength and dynamic control ratio (DCR) of the right leg compared to the 1st and/or 2nd national division players. There were no signs of bilateral strength asymmetry regardless of muscle group tested and contraction mode. Our results suggest that right H strength and DCR could be important for successful volleyball performance. Descriptive data about Q and H muscle function can be used as guidelines for coaches and therapists during training and rehabilitation of male volleyball players.